Prestressed concrete pipes and pipelines - Joshi, N.G (Alpha Science International, 2012)
Covers various aspects of Prestressed Concrete Pipe, right from its inception, design, manufacture, laying, maintenance and more. In this book, spinning process is fully described both from practical and theoretical point of view, which is very useful to all Concrete Pipe Manufacturers.